2021
DOI: 10.4103/joco.joco_57_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes of sponge application versus subconjunctival injection of Mitomycin-C during combined phacoemulsification and trabeculectomy surgery in Asian eyes

Abstract: Purpose: To compare the outcomes of combined phacoemulsification–trabeculectomy surgery with intraoperative sponge-applied versus subconjunctival injection of mitomycin-C (MMC) in Asian eyes. Methods: This was a retrospective review of 95 eyes that consecutively underwent combined phacoemulsification–trabeculectomy surgery in a tertiary eye center in Singapore from January 2013 to June 2014. Data collected included intraocular pressure (IOP), best corrected visual acuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…One of the major risk factors for decreasing CECD after trabeculectomy is MMC (57). Very few clinical studies investigated the effect of intra-Tenon injection of MMC on endothelial cell count (18)(19)(20)38). Overall, no differences in endothelial cell count between MMC-soaked sponge group and intra-Tenon injection of MMC group were found.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…One of the major risk factors for decreasing CECD after trabeculectomy is MMC (57). Very few clinical studies investigated the effect of intra-Tenon injection of MMC on endothelial cell count (18)(19)(20)38). Overall, no differences in endothelial cell count between MMC-soaked sponge group and intra-Tenon injection of MMC group were found.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the sub-Tenon injection of MMC is considered to be a safe and effective alternative to the conventional soaked sponge method. This method may produce more favourable bleb morphology after trabeculectomy (20,38). On the other hand, little information is available regarding the concentration and dosage of MMC applied using intra-Tenon injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the method of application may affect the rate of surgical failure and complications, multiple studies have found that it does not result in significant differences. In a study looking at Asian eyes, phacoemulsification-trabeculectomy combined with subconjunctival MMC injection had comparable outcomes to that of sponge-applied MMC, with a similar reduction in IOP at 1, 6, and 12 months postoperatively and a lower postoperative complication rate [ 43 ]. However, MMC injection may lower the need for clinic visits within the first 3 postoperative months and reduce the need for 5-FU intervention when compared to MMC sponge application [ 117 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 99%